2020
DOI: 10.1001/jamasurg.2020.0091
|View full text |Cite
|
Sign up to set email alerts
|

Association of Functional, Cognitive, and Psychological Measures With 1-Year Mortality in Patients Undergoing Major Surgery

Abstract: IMPORTANCE More older adults are undergoing major surgery despite the greater risk of postoperative mortality. Although measures, such as functional, cognitive, and psychological status, are known to be crucial components of health in older persons, they are not often used in assessing the risk of adverse postoperative outcomes in older adults.OBJECTIVE To determine the association between measures of physical, cognitive, and psychological function and 1-year mortality in older adults after major surgery. DESI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 30 publications
1
30
0
1
Order By: Relevance
“…As the US population progressively ages, patients' impending PC needs will continue to exceed the number of PC specialists available, thus mandating more surgeonspecific application of PPC skills. The prevalence of PC needs for a given surgical patient varies according to comorbidities, prognosis, acuity, physical and cognitive frailty, and the risks of any proposed procedures (43)(44)(45)(46)(47)(48)(49)(50)(51)(52). In a study of the surgical patient population being treated for advanced pancreatic cancer (where survival is measured in months), one third of the inpatients had no documented discussions about their goals of care or preferred code status (53).…”
Section: An Unmet Needmentioning
confidence: 99%
“…As the US population progressively ages, patients' impending PC needs will continue to exceed the number of PC specialists available, thus mandating more surgeonspecific application of PPC skills. The prevalence of PC needs for a given surgical patient varies according to comorbidities, prognosis, acuity, physical and cognitive frailty, and the risks of any proposed procedures (43)(44)(45)(46)(47)(48)(49)(50)(51)(52). In a study of the surgical patient population being treated for advanced pancreatic cancer (where survival is measured in months), one third of the inpatients had no documented discussions about their goals of care or preferred code status (53).…”
Section: An Unmet Needmentioning
confidence: 99%
“…The authors found a monotonic relationship between an increasing number of impairments and increasing risk of 1‐year mortality following major surgery. In particular, dependence in at least one activity of daily living was significantly associated with 1‐year mortality (adjusted hazard ratio (HR) = 2.76, P = .001) 11 …”
Section: Figurementioning
confidence: 99%
“…In particular, dependence in at least one activity of daily living was significantly associated with 1-year mortality (adjusted hazard ratio (HR) = 2.76, P = .001). 11 Understanding the relationship between frailty and mortality can be helpful when counseling older adults considering surgery, but there are limitations to only considering mortality as an outcome. In our surgical urology practice, older adults display less interest in length of life and instead ask probing questions about the hospitalization itself in the short term and the chances of returning to baseline preoperative function in the long term.…”
mentioning
confidence: 99%
“…Die präoperative Erfassung von funktionellen, kognitiven und psychologischen Einschränkungen ist auch deshalb von wesentlicher Bedeutung, da sie ein wesentlicher Risikofaktor für ein vermindertes 1-Jahres-Überleben nach großen chirurgischen Eingriffen darstellt [38].…”
Section: Empfehlungen Zur Prävention Des Postoperativen Delirs Empfehlungsgradunclassified